Development of stem cell ethics and legislation in the world and in Pakistan; a narrative review - Alvina Farhat; Danish Ali; Sana Zeeshan (Journal of the Pakistan Medical Association, 2023)
Stem cells can transform into specialized types of cells, and their capability of self-renewal is limitless. The advancements in stem cell therapy have encountered various hurdles. Considering the massive scope of stem cells applications in health, an effective regulation and monitoring system should be implemented. It is important to ensure that stem cell research projects in Pakistan work closely with the ethics committees as respecting human rights are of paramount importance. It is also necessary that the ethics and legislation guidelines are reviewed, updated, and monitored effectively at every evolving step. Keywords: Stem cells, Research, Transplantation, Legislation, Guidelines